Roman water law in rural Africa: the unfinished business of colonial dispossession - van Koppen, Barbara; Zaag, P. van der; Manzungu, Emmanuel; Tapela, B. (Informa UK Limited, 2014)
This paper discusses four questions about the recent water law reforms in Sub-Saharan Africa, which strengthen permit systems. First, do permit systems continue to dispossess rural small-scale users, as intended by European colonizers who introduced principles of Roman law? Second, is it wrong to assume that one can convert one legal system (customary water rights) into another legal system (permits) in the short term? Third, do current permit systems discriminate against small-scale users? And lastly, do fiscal measures ingrained in permits foster rent seeking and strengthen water resources as a commodity for nationals and foreigners who can pay? As all the answers are positive, the paper concludes by recommending measures to recognize and protect small-scale water users and render state regulation more realistic.